2007
DOI: 10.1525/jer.2007.2.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Applying Research Ethics Guidelines: The View from a Sub-Saharan Research Ethics Committee

Abstract: Considerable variation has been demonstrated in applying regulations across research ethics committees (RECs) in the U.S., U.K., and European nations. With the rise of international research collaborations, RECs in developing countries apply a variety of international regulations. We conducted a qualitative descriptive pilot study with members of the national REC in Malawi to determine criteria they use to review research, and their views on international collaborations. Qualitative content analysis demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…There was substantial methodological heterogeneity as most studies did not measure the same variables, thus precluding rigorous comparison of outcomes of most studies. The sample of RECs described in each article reviewed varied from 1 (Henderson, Corneli, Mahoney, Nelson, & Mwansambo, 2007) to 31 in 18 countries (Nyika, Kilama, Chilengi, et al, 2009; Nyika, Kilama, Tangwa, et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was substantial methodological heterogeneity as most studies did not measure the same variables, thus precluding rigorous comparison of outcomes of most studies. The sample of RECs described in each article reviewed varied from 1 (Henderson, Corneli, Mahoney, Nelson, & Mwansambo, 2007) to 31 in 18 countries (Nyika, Kilama, Chilengi, et al, 2009; Nyika, Kilama, Tangwa, et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies described the history of African RECs (Henderson et al, 2007; Kass et al, 2007; Oyedeji, 2011; Rwabihama, Girre, & Duguet, 2010). A survey of 20 African RECs reported that 9 countries had established RECs in the 1980s, whereas the other 11 were created during the period 1995 to 2003 (Rwabihama et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation and application of ethical principles may differ from one society to another. This is not limited to the situation in the Middle East, but also to other areas in the developing world, such as Africa [29]. Issues such as research on women, informed consent, and breaches of confidentiality require more attention in the guidelines and applications of research in the Middle East [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Publication authorship, the named principal investigators and grant holders for funding applications, staff remuneration policies, tax exemption for foreign researchers and the ownership of samples and data have all been presented as areas where current inequalities undermine equal partnerships and collaborations [ 14 , 15 , 16 ]. It has been argued, that the term ‘collaboration’ can sometimes mask or exacerbate such problems [ 17 , 18 ]. For instance, a recent examination of publications, resulting from global health research collaborations between American and European scientists and those in Central Africa, found that the most frequent role for African scientists was in providing samples and conducting fieldwork not research design [ 19 ].…”
Section: Introductionmentioning
confidence: 99%